Diffuse pattern of bone marrow involvement on magnetic resonance imaging is associated with high risk cytogenetics and poor outcome in newly diagnosed, symptomatic patients with multiple myeloma: A single center experience on 228 patients - Moulopoulos, L.A.; Dimopoulos, M.A.; Kastritis, E.; Christoulas, D.; Gkotzamanidou, M.; Roussou, M.; Koureas, A.; Migkou, M.; Gavriatopoulou, M.; Eleutherakis-Papaiakovou, E.; Gika, D.; Koutoulidis, V.; et al. (American Journal of Hematology, 2012)
Magnetic Resonance Imaging (MRI) and specific cytogenetic abnormalities offer important prognostic information for myeloma patients. However, limited data are available about the association between cytogenetic abnormalities and MRI patterns of marrow infiltration. To address this issue, we analyzed 228 consecutive newly diagnosed, symptomatic patients who were diagnosed and treated in a single center. On bone marrow MR images, 95 (41%) patients had diffuse, 94 (41%) had focal, 35 (15%) were normal, and 4 (1.7%) patients had variegated pattern of marrow infiltration. High risk cytogenetics were more commonly observed with diffuse MRI pattern (50% vs. 31% in focal and normal patterns). Patients with diffuse MRI pattern had poorer survival compared to others and responded better to novel agent-based therapies than to conventional chemotherapy (objective response: 88% vs. 46%, P < 0.001). There was a significant improvement of patients' survival with a diffuse MRI pattern when treated upfront with novel agents compared to conventional chemotherapy (47 vs. 24 months; P < 0.001). Diffuse MRI pattern along with ISS-3 and high risk cytogenetics could identify a very high risk group of patients with extremely poor median survival (21 months) and an only 35% probability of 3-year OS. Our study shows that symptomatic myeloma patients with a diffuse MRI pattern at diagnosis very often show high risk cytogenetic abnormalities and are benefiting from upfront novel agent-based therapies. Diffuse MRI pattern in combination with high risk cytogenetics and ISS-3 can identify a subset of myeloma patients with very poor prognosis who may need innovative treatment strategies and possibly more aggressive therapies. © 2012 Wiley Periodicals, Inc..